Assessment of age-related differences in decomposition-based quantitative EMG in the intrinsic hand muscles: A multivariate approach. Issue 9 (September 2020) - Tsang, Philemon; MacDermid, Joy C.; Miller, Thomas A.; Doherty, Timothy J.; Ross, Douglas C.
Highlights: Multivariate analysis of surface and intramuscular EMG showed large differences between age groups. Surface and intramuscular EMG show decreases in motor unit number estimation and stability in older adults. Multivariate analysis of DQEMG may identify age-related hand neuromuscular changes. Abstract: Objective: Decomposition-based quantitative electromyography (DQEMG) is one method of measuring neuromuscular physiology in human muscles. The objective of the current study is to compare the neuromuscular physiology of a typical aging population in the intrinsic hand muscles. Methods: Measurements of DQEMG were detected with a standard concentric needle and surface EMG from the intrinsic hand muscles. DQEMG was obtained from the first dorsal interosseous (FDI), the abductor digiti minimi (ADM) and fourth dorsal interosseous (4DI). Multivariate analysis of variance (MANOVA) were performed for the surface and intramuscular EMG measures to identify age differences in motor unit properties. Results: Large differences were observed between the age groups for the canonical intramuscular and surface EMG variables. Older adults demonstrated a large decrease in motor unit number estimation in the ADM and FDI. Likewise, medium to large decreases in motor unit stability were observed in the FDI, ADM and 4DI. Conclusions: With aging, there are decreases in motor unit number estimation and stability in the intrinsic hand muscles. Using a multivariate approach allows for age-related differences and the relationship between the variables to be further elucidated. Significance: Multivariate analysis of DQEMG may be useful for identifying patterns of change in neuromuscular physiology with age-related changes to hand musculature. This may potentially lead to future prognostic biomarkers of age-related changes to hand muscles.